Distribution of silver-fir (Abies alba Mill.) in the Sudeten Mts. - Filipiak, Maciej (Biodiversity: Research and Conservation, 2006)
This paper presents the assessments concerning the vertical distribution, exposure, slope inclination and land relief of silver-fir localities. The current distribution of fir trees suggest that in the past, Abies alba was widespread in the Sudety Mts. at the altitude range 350-800 m. At altitudes of up to 800 m, the number of localities in each zone is often proportional to the total forest area in the zone. Above 800 m, fir trees are now very rare. The studied species is in general similarly frequent in localities with various exposure and degree of slope. It prefers concave landforms (valleys, concave slopes). It can be concluded that the studied species occurs in a wide range of habitats in the Sudeten Mts. This suggests that its withdrawing from the Sudetes is not of natural origin. Main cause of this process is related rather with strong interference of man in forest stand composition.